The Drama of Doctrine: A Canonical Linguistic Approach to Christian Theology – Kevin J. Vanhoozer - Webb, Stephen H. (Reviews in religion and theology, 2006)
Book reviewed: The Drama of Doctrine: A Canonical Linguistic Approach to Christian Theology, Kevin J. Vanhoozer, Westminster John Knox Press 2005 (0-6642-2327-3), xv + 487 pp., $25.00